PERSONAL NAVIGATION: EXTENDING MOBILE MAPPING TECHNOLOGIES INTO INDOOR ENVIRONMENTS - GREJNER-BRZEZINSKA, D. A.; TOTH, C. K.; MARKIEL, J. N.; MOAFIPOOR, S.; CZARNECKA, K. (Boletim de Ciências Geodésicas, 2009)
This paper discusses some unconventional methods for indoor-outdoor navigation, based on the integration of self-contained sensors, including GPS, IMU, digital barometer, magnetometer compass, and a human locomotion model. The human locomotion model is used as navigation sensor and it is handled by Artificial Intelligence (AI) techniques that form an adaptive knowledge-based system (KBS), which is trained during the GPS signal reception, and is used to support navigation under GPS-denied conditions. A complementary technique used in our solution, which facilitates indoor navigation, is the image-based method (Flash LADAR). In this paper, the system design and an example performance analysis in the mixed indoor-outdoor environment are presented.